The cicada (Hemiptera: Cicadidae) fauna of the Lesser Antilles sensu lato with the description of two new species, two new combinations, and a key to species - Sanborn, Allen F. (Zootaxa, 2024)
A summary and the known distributions of the cicadas of the Lesser Antilles sensu lato are provided. Fidicina guadeloupensis n. sp. from Guadeloupe and Herrera castaneanigricula n. sp. from Martinique are described as new. Carineta acclivis Sanborn, 2017b and Carineta martiniquensis Davis, 1934 are reassigned to become Herrera acclivis (Sanborn, 2017b) n. comb. and Herrera martiniquensis (Davis, 1934) n. comb. A total of 23 species, 13 genera, four tribes and two subfamilies are known to inhabit the various island chains with seven species being endemic to a single island. The majority (15 species) is found in the Republic of Trinidad & Tobago. More than half of the genera (eight) and species (12) represented in the Lesser Antilles are members of the Fidicinini Distant, 1905a. Herrera Distant, 1905b is the most diverse genus with five species recorded from the region, Proarna Stål, 1864 is also well represented with four species. Proarna hilaris (Germar, 1834) is the species with the greatest range expanding from the Virgin Islands to Trinidad in the Lesser Antilles. Finally, a key to the known cicada species of the Lesser Antilles is provided.